Average effectiveness of corporate income tax on the example of companies listed on the Belgrade Stock Exchange - Miloš Đaković; Milica Inđić; Danica Cicmil (Anali Ekonomskog fakulteta u Subotici, 2022)
The fiscal policy of a country is a crucial source of successful and normal functioning of that country's economy. The implications of fiscal policy can be reflected in both the private and the functioning of the public sector of a country's economy. Public finance is an area of ​​economics that deals with the analysis of tax policy and government spending policy. One of the important areas of public finance research is corporate income tax. Corporate income tax is a direct tax imposed at the national level for the purpose of taxing the profits of certain companies, whether state-owned or privately owned. The aim of this paper is to look at the actual amount of profit tax paid, ie by observing the profit before taxation of companies listed on the Belgrade Stock Exchange. considers the effective tax rate of companies and points out the deviation of the same from the legally prescribed corporate income tax rate in the Republic of Serbia and to consider the implications of corporate income tax on the company's business results. The paper presents graphical and tabular representations of the effective tax rates of each company as well as the average effective tax rate of companies listed on the Belgrade Stock Exchange in relation to the law in the period from 2013 to 2020 in the Republic of Serbia. Finally, a statistical analysis of the presented results is given in order to more precisely understand the deviation of the effectiveness of corporate income tax of companies listed on the Belgrade Stock Exchange as well as the analysis of the correlation between the growth of the average pre-tax profit and the growth of the average effective corporate income tax rate.